2014
DOI: 10.1039/c3dt52553h
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 2-hydroxy-2-methylpropanoate derivatives of magnesium and zinc. The effect of chelation on the homo- and copolymerization of lactide and ε-caprolactone

Abstract: The preparation, single crystal and molecular structures of the compounds (BDI)Mg(OCMe2COOEt)(L) are described where BDI = 2-[(2,6-diisopropylphenyl)amino]-4-[(2,6-diisopropylphenyl)imino]pent-2-ene and L = pyridine (py) and 4-dimethylaminopyridine (DMAP). In the solid-state the molecules have five coordinate Mg(2+) ions that may be considered as derived from a trigonal bipyramid where the chelating BDI and OCMe2COOEt ligands span equatorial-axial sites. IR spectroscopic data obtained in CH2Cl2 indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…This is in agreement with results found for the copolymerization of LLA and CL using Zn and Mg complexes, where the chelating effect of the lactate unit was shown to be responsible for the inability of these complexes to facilitate copolymerization, while both monomers were efficiently homopolymerized. 28,29 Since the PLLA growing chain showed no reactivity toward PDL and the ROP of a strainless cyclic ester such as PDL resembles the transesterification of a linear chain, it was assumed that a growing PLLA chain would not be able to undergo transesterification with a PPDL chain either. Therefore, in an attempt to produce a poly(PDL-block-LLA) copolymer, a sequential feed approach was applied in which first PDL was allowed to polymerize to >94% monomer conversion using 2′ ([PDL]/[2′] = 50), after which varying amounts of lactide (as hot p-xylene solutions) were added.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is in agreement with results found for the copolymerization of LLA and CL using Zn and Mg complexes, where the chelating effect of the lactate unit was shown to be responsible for the inability of these complexes to facilitate copolymerization, while both monomers were efficiently homopolymerized. 28,29 Since the PLLA growing chain showed no reactivity toward PDL and the ROP of a strainless cyclic ester such as PDL resembles the transesterification of a linear chain, it was assumed that a growing PLLA chain would not be able to undergo transesterification with a PPDL chain either. Therefore, in an attempt to produce a poly(PDL-block-LLA) copolymer, a sequential feed approach was applied in which first PDL was allowed to polymerize to >94% monomer conversion using 2′ ([PDL]/[2′] = 50), after which varying amounts of lactide (as hot p-xylene solutions) were added.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…the rate of PLA that is formed is $80% but when L = py or DMAP the conversion is only $30%. We note that in DCM the binding of L toward to the catalytic center suppress the rate of polymerization [5]. In DCM the % of heterotactic (isi, sis) PLA is close to 50%.…”
Section: Rates Of Polymerization Of Lamentioning
confidence: 89%
“…In the ground state the two i Pr groups are equivalent if we obtain a three-coordinate (I) and in a five-coordinate (II) complex as shown in Fig. 1 [3][4][5]. In the four-coordinated metal the i Pr ligands are inequivalent.…”
Section: Introductionmentioning
confidence: 94%
“…Here we observed that our catalyst showed more catalytic activity towards the ROP and taken less time for complete conversion. [47][48][49][50][51][52][53][54][55][56][57][58][59] M n of the PLA was found much higher and narrow MWDs than literature reported magnesium catalysts [47][48][49][50][51]55 but tacticity (P r ) of the PLA was found to be comparatively less than the few other recently reported magnesium catalysts. [47][48][49]58 The variation of M n and MWDs with [M] o /[C] o ratio for the polymerization of rac-LA and L-LA using 1, 5, and 6 were studied next.…”
Section: Ring Opening Polymerizationmentioning
confidence: 99%